2017
DOI: 10.1177/1074248417708618
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Takotsubo Cardiomyopathy

Abstract: Our systematic review showed that over two-thirds of drug-induced TCM cases were due to direct or indirect catecholamine stimulation. The lowest effective dose and shortest duration of catecholamines should be utilized, and alternative therapies should be considered if feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 123 publications
0
44
0
Order By: Relevance
“…Despite the abovementioned conflicting results, TTS has been induced in several clinical cases by the intravenous injection of catecholamines. In 2017, Kido and Guglin analyzed 157 cases of drug-induced TTS and found that 68.2% were catecholamines-related, while 8.9% appeared to be associated with chemotherapy-induced coronary vasospasm [25]. In addition, Abraham et al revealed in 2009 that the intravenous administration of epinephrine or beta-receptor agonists could induce all the characteristic features of TTS, including an elevation of cardiac isoenzyme levels, rapidly reversible cardiac dysfunction, and QTc interval prolongation [26].…”
Section: The Role Of Stress and Catecholamines In Takotsubo Syndromementioning
confidence: 99%
“…Despite the abovementioned conflicting results, TTS has been induced in several clinical cases by the intravenous injection of catecholamines. In 2017, Kido and Guglin analyzed 157 cases of drug-induced TTS and found that 68.2% were catecholamines-related, while 8.9% appeared to be associated with chemotherapy-induced coronary vasospasm [25]. In addition, Abraham et al revealed in 2009 that the intravenous administration of epinephrine or beta-receptor agonists could induce all the characteristic features of TTS, including an elevation of cardiac isoenzyme levels, rapidly reversible cardiac dysfunction, and QTc interval prolongation [26].…”
Section: The Role Of Stress and Catecholamines In Takotsubo Syndromementioning
confidence: 99%
“…106 The protein product of PIK3R3 , phosphoinositide-3-kinase regulatory subunit 3, acts downstream of G-protein-coupled receptors in cardiac function, 107 and is also a target for isoproterenol, which can trigger SCM-like conditions in humans and rodents. 12; 108110…”
Section: Resultsmentioning
confidence: 99%
“…The pathophysiology of Takotsubo cardiomyopathy remains unknown, as does the optimal treatment strategy. 3 Direct and indirect catecholamine stimulation has been associated with its development and progression, 4 supporting the hypothesis that excessive sympathetic stimulation is fundamental to the pathophysiology of the disease. 3 Why certain individuals are susceptible to this process is unclear, as is whether primary pathology or susceptibility resides in the brain, the autonomic nervous system, the myocardium, or all three.…”
mentioning
confidence: 84%